Long-Term Psychosocial Consequences of False-Positive Screening Mammography - Brodersen, John (American Academy of Family Physicians, 2013)
PURPOSE: Cancer screening programs have the potential of intended beneficial effects, but they also inevitably have unintended harmful effects. In the case of screening mammography, the most frequent harm is a false-positive result. Prior efforts to measure their psychosocial consequences have been limited by short-term follow-up, the use of generic survey instruments, and the lack of a relevant benchmark—women with breast cancer. METHODS: In this cohort study with a 3-year follow-up, we recruited 454 women with abnormal findings in screening mammography over a 1-year period. For each woman with an abnormal finding on a screening mammogram (false and true positives), we recruited another 2 women with normal screening results who were screened the same day at the same clinic. These participants were asked to complete the Consequences of Screening in Breast Cancer—a validated questionnaire encompassing 12 psychosocial outcomes—at baseline, 1, 6, 18, and 36 months. RESULTS: Six months after final diagnosis, women with false-positive findings reported changes in existential values and inner calmness as great as those reported by women with a diagnosis of breast cancer (Δ = 1.15; P = .015; and Δ = 0.13; P = .423, respectively). Three years after being declared free of cancer, women with false-positive results consistently reported greater negative psychosocial consequences compared with women who had normal findings in all 12 psychosocial outcomes (Δ >0 for 12 of 12 outcomes; P <.01 for 4 of 12 outcomes). CONCLUSION: False-positive findings on screening mammography causes long-term psychosocial harm: 3 years after a false-positive finding, women experience psychosocial consequences that range between those experienced by women with a normal mammogram and those with a diagnosis of breast cancer.